Degenerated graphite nodules influence on fatigue crack paths in a ferritic ductile cast iron (Fracture and Structural Integrity, 2015)
Focusing on ferritic-pearlitic DCIs, these alloys are characterized by a microstructure that rangesfrom a fully ferritic to a completely pearlitic matrix, and they are widely used for many applications (e.g. wheels,gears, crankshafts in cars, exhaust manifolds, valves, flywheels, boxes bearings, hubs, shafts, valves, flanges,pipelines ...). Considering the graphite elements, their morphology can be considered as degenerated when itsnodularity is too low and this can be due to different causes (e.g., a partially failed nodularization process or awrong inoculant). In this work, a ferritic DCI with degenerated nodules was obtained by means of an annealingtreatment and the fatigue crack propagation resistance was investigated by means of fatigue crack propagationtests performed according to ASTM E647, focusing on the influence of degenerated graphite nodules on thefatigue crack paths. This analysis was performed both analysing the crack path profile by means of a scanningelectron microscope (SEM) and by means of a SEM fracture surfaces analysis.
Keywords: Ferritic-pearlitic ductile cast irons